2012
DOI: 10.1002/hep.24700
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid suppressor cells induced by hepatitis C virus suppress T-cell responses through the production of reactive oxygen species

Abstract: Impaired T-cell responses in chronic hepatitis C virus (HCV) patients have been reported to be associated with the establishment of HCV persistent infection. However, the mechanism for HCV-mediated T-cell dysfunction is yet to be defined. Myeloid-derived suppressor cells (MDSCs) play a pivotal role in suppressing T-cell responses. In this study we examined the accumulation of MDSCs in human peripheral blood mononuclear cells (PBMCs) following HCV infection. We found that CD33+ mononuclear cells cocultured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
187
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(198 citation statements)
references
References 30 publications
(41 reference statements)
9
187
1
Order By: Relevance
“…However, upon treatment with IFN-γ and IL-4, they could eliminate the parasites in a NO-dependent manner. A similar expansion of MDSCs was also seen in Hepatitis C virus (HCV) infections in humans, where T-cell proliferation was suppressed through a ROSmediated mechanism [86].…”
Section: Mdscs In Other Pathological Conditionsmentioning
confidence: 73%
“…However, upon treatment with IFN-γ and IL-4, they could eliminate the parasites in a NO-dependent manner. A similar expansion of MDSCs was also seen in Hepatitis C virus (HCV) infections in humans, where T-cell proliferation was suppressed through a ROSmediated mechanism [86].…”
Section: Mdscs In Other Pathological Conditionsmentioning
confidence: 73%
“…Our findings both in primary human HSC and the LX-2 cell line provide evidence that This may explain why HUH7 cells are unable to induce MDSC despite expressing high levels of catalase because CD44 is absent from noninfected HUH7 cells (38,39). Of note, the concentration of purified catalase used in our monocyte cultures is only likely to be achieved locally when cells are in close proximity (see Fig.…”
Section: Discussionmentioning
confidence: 61%
“…It has been reported that MDSCs presented in viral infectious diseases, autoimmune diseases, tumor, and parasitic infections diseases and inhibited the T cell proliferation (Greten et al, 2011;Tacke et al, 2012;Vollbrecht et al, 2012). However; MDSCs expression about the mechanism and course of the disease for chronic HBV patients was limited.…”
Section: Discussionmentioning
confidence: 99%
“…hepatitis C Viral (HCV) and Acquired Immune Deficiency Syndrome (AIDS) (Tacke et al, 2012;Vollbrecht et al, 2012;Cai et al, 2013;Qin et al, 2013). On the other hand, complications of chronic hepatitis B (CHB), e.g.…”
Section: Introductionmentioning
confidence: 99%